ANALISIS MANAJEMEN PENDIDIKAN DI SLB NEGERI 1 LIMA KAUM - Vicky Rizki Febrian; Zulmuqim Zulmuqim; Himyar Pasrizal (IAIN Batusangkar, 2019)
This study aims to determine the application of management aspects of education in: (1) personnel and student management, (2) curriculum management, and (3) infrastructure management in Lima Kaum 1 SLB. This research is qualitative research with a case study method. Data collection techniques used are: Observation, Interview Method and Documentation. The results of the study revealed: (1) in staffing and student management, it was found that the implementation of management had been carried out in terms of routine activities, but there were still a number of things that had to be corrected namely in terms of organization, function of school leaders and businessmanship , it was found that the school had made every effort in implementing the 2013 Curriculum, but still needed proper and accurate management in its implementation at school and the development of a typical school curriculum so as to improve school quality, (3) in the management of facilities and infrastructure found that administrative management in the procurement of infrastructure facilities it is good, but still needs improvement in terms of planning procurement of facilities that are right on target and management of existing infrastructure.